Characteristics of grounding performance at Taman Bukit Perdana - Abdul Malik, Abdul Mukmin; Mohd Jamail, Nor Akmal; Othman, Nordiana Azlin; ., Muhammad Saufi; Kamarudin, Qamarul Ezani (Penerbit UTHM, 2020)
Grounding system is one of the important part during installation of power systems. The function of grounding system is to enable protection to the power system in case of any current leakage or lightning strike. A grounding system will disconnect the circuit as soon as the fault current flows through the earth [1]. Every potential connection or equipment that may cause the current leakage must be grounded. In a simple way, it can be defined as the system to protect and stabilize the operation for human and equipment during fault conditions.